Effective Osteoporosis Prevention in Nigeria: Implications for Health Education - Anyanwu, Ozioma (International Journal of Human Kinetics, Health and Education, 2023)
Osteoporosis is a disease characterized by low bone mass and loss of bone tissue that may lead to weak and fragile bones. Osteoporosis is often considered to be a condition that frail elderly women develop. However, the damage from osteoporosis begins much earlier in life. Because peak bone density is reached at approximately 25 years of age, it is important to build strong bones by that age, so that the bones will remain strong later in life. Adequate calcium intake is an essential part of building strong bones. According to the international osteoporosis foundation in an extrapolated statistic, nearly 2million people in Nigeria has osteoporosis, In the United States, nearly 10 million people already have osteoporosis. Another 18 million people have low bone mass that places them at an increased risk for developing osteoporosis. As our population ages, these numbers will increase. About 80% of those with osteoporosis are women. Of people older than 50 years of age, one in two women and one in eight men are predicted to have an osteoporosis-related fracture in their lifetime. Significant risk has been reported in people of all ethnic backgrounds. Osteoporosis is a worldwide health concern. Preventing osteoporosis, and subsequent fractures, has become a goal of many health care practitioners.